2015
DOI: 10.1021/jp5129673
|View full text |Cite
|
Sign up to set email alerts
|

Role of Organics in Regulating ClNO2 Production at the Air–Sea Interface

Abstract: We report measurements of the product yield for nitryl chloride (ClNO2) production following the reactive uptake of dinitrogen pentoxide (N2O5) to a wide variety of ambient seawater samples as well as seawater mimics. The ClNO2 yield, as measured for ambient seawater collected from both coastal and open ocean waters, was found to be both insensitive to chlorophyll-a, a marker for biological activity, and significantly lower (0.16-0.30) than that expected for equivalent salt-containing solutions (0.82 ± 0.05). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 50 publications
10
71
3
Order By: Relevance
“…This finding was attributed to the previously unrecognized atmospheric reaction path, where organic nitrification reactions between NO 2 + and aromatic rings in humic substances or proteins suppress the production of ClNO 2 (Figure 3d). 35 Previous studies in marine environments have shown a change in cloud properties in regions of phytoplankton blooms. It has been hypothesized that the critical factors that drive such changes are the relative organic content and composition of SSA particles as well as their size distributions and number concentrations.…”
Section: ■ Chemistry-driven Interactions Betweenmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was attributed to the previously unrecognized atmospheric reaction path, where organic nitrification reactions between NO 2 + and aromatic rings in humic substances or proteins suppress the production of ClNO 2 (Figure 3d). 35 Previous studies in marine environments have shown a change in cloud properties in regions of phytoplankton blooms. It has been hypothesized that the critical factors that drive such changes are the relative organic content and composition of SSA particles as well as their size distributions and number concentrations.…”
Section: ■ Chemistry-driven Interactions Betweenmentioning
confidence: 99%
“…34 Segment D shows a previously unrealized competition between aromatic organics and Cl − for NO 2 + resulting from N 2 O 5 uptake to a surface. 35 integrated methodologies. Thus, simple systems informed by results from complex systems have been utilized to establish model chemical systems that can be leveraged to provide parametrizations of SSA chemistry that improve the understanding of real world complexity in the future.…”
Section: Accounts Of Chemical Researchmentioning
confidence: 99%
“…A value of k 4 /k 2 of 450 is presently recommended (Ammann et al, 2013), but may be modified for systems with a significant concentration of aromatics which can also react with hydrated nitronium ions (Ryder et al, 2015). Nitrate formed in the uptake of N 2 O 5 can partition to the gas phase as nitric acid or remain in the particle depending on the pH, available ammonia/ammonium and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[304][305][306] In the atmosphere, they can alter the exchange between the gas phase and clouds, fogs and particles, [307][308][309][310][311][312][313] change the kinetics of reactions such as the hydrolysis of NO 2 (ref. 173) and the oxidation of organics, 268,314,315 and alter ion composition and chemistry at the interface.…”
Section: Organicsmentioning
confidence: 99%
“…555,560 Organic coatings also appear to decrease N 2 O 5 uptake on particles, although this may be sensitive to the relative amounts of water present (and hence relative humidity) as well as the viscosity of the organic coating. 312,313,556,[561][562][563][564][565][566][567] If chloride ions are present, there is a competing reaction to form nitryl chloride, ClNO 2 . [568][569][570][571][572][573] It is interesting that the chloride ion reaction occurs at the interface, while that with water occurs deeper into the bulk of the particle.…”
Section: Biogenic-anthropogenic Synergies In the Anthropocenementioning
confidence: 99%